2009
DOI: 10.1088/0960-1317/19/6/065020
|View full text |Cite
|
Sign up to set email alerts
|

Friction characteristics of the curved sidewall surfaces of a rotary MEMS device in oscillating motion

Abstract: A MEMS device with a configuration similar to that of a micro-bearing was developed to study the friction behavior of the curved sidewall surfaces. This friction-testing device consists of two sets of actuators for normal motion and rotation, respectively. Friction measurements were performed at the curved sidewall surfaces of single-crystal silicon. Two general models were developed to determine the equivalent tangential stiffness of the bush-flexure assembly at the contact point by reducing a matrix equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Also, its elastic modulus (E) and roughness do not vary, unlike those of a polysilicon structural film, which depend on the conditions used to deposit and anneal the polysilicon structural film and hence vary from wafer to wafer and sometimes even on the same wafer from chip to chip [35,36]. Since both E and roughness of the contacting sidewall surfaces influence their friction and wear characteristics, variation in them can result in inconsistent results [1,4,6,8,21,22,24,27]. Therefore, owing to the usage of a SCS film as its device layer, the results obtained using the sidewall friction and wear test microinstrument reported in this paper are more consistent than those obtained using the polysilicon-based sidewall friction and wear test microinstruments reported previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, its elastic modulus (E) and roughness do not vary, unlike those of a polysilicon structural film, which depend on the conditions used to deposit and anneal the polysilicon structural film and hence vary from wafer to wafer and sometimes even on the same wafer from chip to chip [35,36]. Since both E and roughness of the contacting sidewall surfaces influence their friction and wear characteristics, variation in them can result in inconsistent results [1,4,6,8,21,22,24,27]. Therefore, owing to the usage of a SCS film as its device layer, the results obtained using the sidewall friction and wear test microinstrument reported in this paper are more consistent than those obtained using the polysilicon-based sidewall friction and wear test microinstruments reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, owing to the variable material properties and surface roughness of polysilicon structural films, the results obtained in all of the above-mentioned studies showed significant device-to-device scatter, which made it difficult to draw a meaningful conclusion [4,6,8,21,22,24]. Only four SCS-based friction test devices have been reported to date [1,[26][27][28][29]. The first SCS-based friction test device was reported in 1995, by Prasad et al, who used them to study the friction characteristics of oxide coated sidewalls [28].…”
Section: Introductionmentioning
confidence: 99%
“…In our design, we employ in-plane electrostatic comb-drive pair actuation mechanism for its simplicity and relative ease of fabrication [ 22 , 23 , 24 ]. The schematic of the electrostatic actuation based PTG is depicted in Figure 2 .…”
Section: Pitch Tunable Diffraction Grating (Ptg)mentioning
confidence: 99%
“…In the current design, the in-plane electrostatic comb-drive pair actuation mechanism was employed for its simplicity and relative ease of fabrication [124,125,126].…”
Section: Micromechanical Implementationmentioning
confidence: 99%